Sexual Dysfunction in Chronic Urticaria: A Systematic Review - Sarah E. Park; Elaine Ma; Caitlyn Dagenet; Maria A. Aleshin; Heather M. Holahan; Vivian Y. Shi; Jennifer L. Hsiao (Dermatology and Therapy)
Abstract Introduction Chronic urticaria (CU) is frequently a debilitating skin condition characterized by recurrent and spontaneous wheal and flares with significant impact on quality of life. This systematic review examines the impact of CU on sexual health. Methods A systematic review using PubMed, Embase, Web of Science, and Cochrane library databases was conducted for articles on sexual health in chronic urticaria. Results The database search produced 741 articles, of which 14 articles met inclusion criteria. Study design, patient demographics, disease characteristics, measures used to assess sexuality or sexual function, and study results were independently extracted for each article by two researchers. Any discrepancies were resolved to consensus by a third reviewer. Sexual dysfunction was common in patients with CU and its severity is associated with increased disease activity and poor disease control. Conclusion Sexual dysfunction is common in patients with CU, and it negatively affects their quality of life (QoL), body image, sleep quality, and mental health. Incorporating sexual health assessments into CU trials will allow for valuable insights into efficacy of study medications on this important QoL domain. Increased awareness of sexual impairment in CU is needed to provide comprehensive care.